Leveraging Information Systems, Applications, and Technologies for Energy-Efficient, Resource-Saving Sustainable Innovation and Strategic Development in The Hospitality ‎Industry: Interactions BetweenCorporate Law and Public ‎Administration - Hutsaliuk, Oleksii; Levchenko , Anna; Panchyshyn , Anton; Abliazov , Denys; Buhaieva , Mariia; Pantielieieva, Iryna; Chen, Minglei (International Journal of Basic and Applied Sciences, 2025)
The contemporary hospitality industry faces significant pressures to enhance sustainability and improve strategic and crisis management ‎amidst dynamic market conditions. This study explores the pivotal role of Information Systems (IS), applied technology, and specific ‎software applications in enabling energy-saving and resource-saving innovations within this sector. Moving beyond purely economic ‎models, we investigate how technology facilitates operational efficiency, enhances guest experiences related to sustainability, and supports ‎managerial decision-making. Adopting a qualitative exploratory approach based on thematic analysis of potential industry insights, this paper ‎examines the types of IS and technologies implemented (e.g., Building Management Systems, IoT, Guest-facing Apps), their perceived ‎benefits (cost reduction, enhanced reputation, improved resource allocation), and associated implementation challenges (integration, cost, ‎user adoption, skills gaps). We also consider the influence of corporate law and public administration frameworks on technology adoption ‎patterns. The findings suggest that strategic deployment and effective management of IS and technology are crucial for achieving ‎sustainability goals and enhancing organizational resilience in hospitality. This study provides insights for managers and technologists on ‎leveraging technology applications for competitive advantage and sustainable operations‎.
Keywords: Information Systems; Applied Technology; Hospitality Industry; Energy Efficiency; Resource Saving; Strategic Development; Innovation; ‎Public Admin-istration